Evaluación del comportamiento en poscosecha, de tres hibridos de pimiento (capsicum annuum) con tres temperaturas y dos atmósferas modificadas en la provincia de Cotopaxi - López Jiménez, Lilia Patricia (2015)
The investigation “ EVALUATION OF BEHAVIOUR IN POSTHARVEST, OF THREE HYBRIDS OF PEPPER (Capsicum annuum) WITH THREE TEMPERATURES AND TWO MODIFIED ATMOSPHERES IN COTOPAXI PROVINCE” it was realized in the province of Cotopaxi, parish Eloy Alfaro neighborhood Salache Bajo in the laboratory of postharvest of the carrer of Agronomic Engineering, where three temperatures were proved, ambient, 4°C, and 8°C, three hybrids of pepper and two modified atmospheres: wax and roll pack, with 18 treatments by three repetitions, the indicators to evaluate were: acidity (PH), solubles solids (°BRIX) and firmmess of the fruit (lbfxcm2-1); the following results were: The best temperature of conservation 4°C, best hybrid: hybrid 3, best modified atmosphere: roll pack: the best treatment is T2H3A2 ( temperature 4°C, hybrid 3 and tray with roll pack) where the vegetable preserves its physical and nutritious properties for more time suitable for commercialization.